Initial Development of an Immediate Implantation Model in Rats and Assessing the Prognostic Impact of Periodontitis on Immediate Implantation - Yingying Wang; Ximeng Cao; Yingyi Shen; Qi Zhong; Yujie Huang; Yifan Zhang; Shaohai Wang; Chun Xu (Bioengineering, 2023)
Background: To establish an immediate implantation rat model and to evaluate the effects of pre-existing periodontitis and two different socket rinse solutions on immediate implantation prognosis. Methods: Sprague-Dawley (SD) rats were randomly divided into three groups before immediate implantation, including the control group, the group with experimentally induced periodontitis (EP), in which rats have been experimentally induced periodontitis before implantation, and the group with induced periodontitis and with extraction sockets rinsed with three percent H2O2 (EP-H2O2), in which rats have been induced periodontitis before implantation, and extraction sockets were rinsed with three percent H2O2. Periodontitis was induced by ligating the thread around the molars for four weeks. Six weeks after titanium alloy implants were self-tapped and left to heal transmucosally, maxillae were dissected after the clinical examination to perform micro-CT and histological analysis. Results: An immediate implantation model was successfully built in rats. There was no significant difference in implant survival rates between the EP and control groups. However, the clinical examination results, micro-CT analysis, and histological analysis in EP and EP-H2O2 groups showed a significantly worse prognosis than in the control group. Three percent H2O2 showed a similar effect with saline. Conclusion: This study presented a protocol for establishing a rat immediate implantation model and showed that periodontitis history might negatively affect the prognosis of immediate implantation. These findings urge caution and alternative strategies for patients with periodontal disease history, enhancing the long-term success of immediate implantation in dental practice. Additionally, the comparable outcomes between 3% H2O2 and saline suggest the use of saline as a cost-effective and safer alternative for implant site preparation in dental practice.